Eksperimen Bahan Makanan Sebagai Alternatif Cat Warna Air - Fitri Chandra; Onggal Sihite; Mesra Mesra (Mahesa Research Center, 2021)
This research aims to describe the process of creating water color paints and the resulting colors made of foodst materials. The making of this water color paint through several stages, such stages are, observation, exploration, experimental, and quality testing. This experiment focused on foodstings as dye paint making materials. The exploration stage is about the materials used as additives, pigments, solvents, and binders in paints. Experimental stages in the form of making groceries into dye paints. The quality test stage is the process of comparing the quality of the experiment's color paint and the factory-made color paint. The concept of making color paint explores ingredients from food namely, kanji flour, baking soda, vinegar, food coloring, and water. And aids like, bowls and spoons, plastic containers, and toothpicks. The paint is realized into the form of a painting using aquarel painting technique.